Analisis Pengaruh Pelayanan dan Produk Terhadap Pengambilan Keputusan Pemakaian Jasa Maskapai PT.Garuda Indonesia di Bandara Adi Soemarmo Boyolali - Rinta Arum Sari (Jurnal Multidisiplin Madani, 2022)
The purpose of this study was to determine the effect of services and products on decision making using the services of the airline Pt. Garuda Indonesia at Adi Soemarmo Boyolali Airport. By considering the aspects of comfort and safety when using air transportation.This research is a quantitative research. The method used in this research is a questionnaire method with a questionnaire instrument and the research subjects used are service users at Adi Soemarmo Boyolali Airport, totaling 92 people. Data analysis and hypothesis testing were performed with IBM SPSS 22 statistics using multiple linear regression analysis.The results showed that H1 and H2 were accepted. meaning that services and products affect the decision to use the services of an airline Pt. Garuda Indonesia at Adi Soemarmo Boyolali Airport. Where the tcount value of the service variable is 2.809 and the tcount value of the product variable is 3.286.